Age Variation in Mating Strategies and Partner Preferences: Beliefs versus Reality. - VandenHeuvel, Bailey; Vander Wyst, Maria (My University, 2009)
We conducted three studies to (1) investigate individuals' beliefs about change in mating desires over the course of emerging adulthood and (2) determine whether those beliefs reflect actual variation in mating desires among emerging adults of varied ages (late teens through twenties).
Color poster with text and graphs.
Keywords: Mate selection--Research; Mate selection--Attitudes; Mate selection--Sex differences; Posters